Automating the "Material examined" section of taxonomic papers to speed up species descriptions - Brown, Brian V. (Zootaxa, 2013)
There has been much discussion of the “taxonomic impediment” and of speeding up descriptive taxonomy (e.g., Hoagland 1996; Wheeler et al. 2004; Godfray 2007; Ebach et al. 2011). It is claimed that the rate of species description is being impeded by the lack of cyber infrastructure resources (Wheeler 2008, for example). Other factors, such as lack of funding, lack of recognition for taxonomic work, the small number of researchers, and distractions from research (committee work, teaching, administration) are also likely sources of slow rates of species description, but some aspects of traditional species description could be improved upon.